High prevalence of TB disease in contacts of adults with extrapulmonary TB. Issue 8 (16th November 2017) - Wingfield, Tom; MacPherson, Peter; Cleary, Paul; Ormerod, L Peter
Abstract : UK guidelines no longer recommend routine screening of household contacts of adult patients with extrapulmonary TB (EPTB). From 27 March 2012 to 28 June 2016, we investigated the prevalence of active TB disease in household contacts of 1023 EPTB index cases in North West England, and compared estimates with: published new entrant migrant screening programme prevalence ( 147/100 000 person-years); London-based contact screening data (700/100 000 contacts screened); and National Institute for Health and Care Excellence (NICE) new entrant TB screening thresholds (TB prevalence >40/100 000 people). Active TB disease prevalence in EPTB contacts was 440/100 000 contacts screened, similar to UK new entrant screening programmes, London EPTB contact prevalence and >10 times NICE's threshold for new entrant screening. The decision to no longer recommend routine screening of EPTB contacts should be re-evaluated and cost-effectiveness analyses of screening strategies for EPTB contacts should be performed.